2006
DOI: 10.1590/s1516-31802006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Isolated systolic hypertension: primary care practice patterns in a Nigerian high-risk subpopulation

Abstract: CONTEXT AND OBJECTIVE: Hypertension management and risk prediction based on diastolic blood pressure may be of little value for older people and people with isolated systolic hyper-tension (ISH). This study investigated primary care practice patterns in ISH management in a Nigerian high-risk subpopulation. DESIGN AND SETTING: Three-year retrospective cohort review of outpatient medical records at a state primary health care facility in southwestern Nigeria. METHODS: ISH was defined according to international g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Within a broader intervention to address severe shortage of healthcare workforce must be efforts to address physician-related factors, including indifference towards elevated blood pressure among treated patients and insufficient awareness to treatment guidelines [47,48]. For example in southwestern Nigeria, Ono and colleagues [49] reported failure of primary care physicians to intensify antihypertensive medications. Moreover, they reported a tendency to keep patients on monotherapy or “no drug treatment” even in cases of repeated visits to the clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Within a broader intervention to address severe shortage of healthcare workforce must be efforts to address physician-related factors, including indifference towards elevated blood pressure among treated patients and insufficient awareness to treatment guidelines [47,48]. For example in southwestern Nigeria, Ono and colleagues [49] reported failure of primary care physicians to intensify antihypertensive medications. Moreover, they reported a tendency to keep patients on monotherapy or “no drug treatment” even in cases of repeated visits to the clinic.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Health systems in SSA must overcome multiple challenges to effectively manage the rising epidemic of hypertension and diabetes, including medication shortages, lack of diagnostic equipment, poor patient and physician knowledge and training, absent or inadequate treatment guidelines, cost of long-term treatment, and lack of effective screening programs, among others. [5][6][7][8][9][10][11] In Tanzania, for example, primary care provision is limited and in 2012 there were only 7.1 health care workers per 10,000 people, 12,13 an inadequate number to effectively manage and prevent NCDs. Furthermore, recent surveys of Tanzanian health care facilities have demonstrated that many lack basic functioning diagnostic equipment such as blood pressure cuffs or glucometers, and the majority of facilities lack protocols for NCD management.…”
Section: Introductionmentioning
confidence: 99%
“…18 studies were quantitative in nature, four qualitative [ 30 – 33 ], and two were mixed-method study [ 34 , 35 ]. Of the 18 studies, one was a cluster-randomized trial [ 36 ]; 4 were cohort studies [ 37 40 ]; one of which was retrospective [ 39 ] alongside 2 other retrospective studies [ 41 , 42 ] and one mixed-method retrospective study [ 35 ]; 10 were cross-sectional studies. Majority of the studies were carried out in South Africa (n = 9) and in Nigeria (n = 8), 4 in Cameroon, while the rest in the Democratic Republic of Congo, Ethiopia, Ghana, and Tanzania.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, physician inertia and/or failure to intensive antihypertensive medication are common in the region. In southwestern Nigeria, Ono and colleagues [ 39 ] observed that physicians increasingly “ placed patients on monotherapy or "no drug treatment" ,. even in cases of uncontrolled systolic blood pressure .…”
Section: Resultsmentioning
confidence: 99%